RESPON TANAMAN MELATI PUTIH (Jasminum sambac L. W. Ait.) TERHADAP BEBERAPA KONSENTRASI PACLOBUTRAZOL - Utari, Prima - (STKIP PGRI Sumbar, 2014)
Jasmine is regarded as an ornamental plant that is widely used in industry, especially in the manufacture of jasmine oil, and its worth is about US 5000/liter. However, it takes such a long time for Jasmine to produce flowers. In order to accelerate the Jasmine efflorescence process, paclobutrazol was given. This research was about the Response of White Jasmine (Jasminum sambac L. W. Ait.) on Paclobutrazol. This research was conducted from May to June 2014 in plantation house of STKIP PGRI Sumatera Barat and in the Physiology of Plants Laboratory of Biology Department of FMIPA UNP Padang. This research was intended to see the responses given by white jasmine (Jasminum sambac L. W. Ait.) on Paclobutrazol. This research was conducted by using complete random design consisting of 6 treatments and 4 repetitions. The result of the research indicated that paclobutrazol had high impact on the size of plant, number of leaves, chlorofile contained and accelerate the growth of the shoots. Paclobutrazol, however, could not elongate the phase of life of white jasmine (Jasminum sambac L. W. Ait.).